(untitled) (Journal of Environmental Science Studies, 2022)
Water quality analysis is an essential component of water supply globally. This study analyzed drinking water quality at the tap in the Wa Municipality of Ghana. Bacteriological, physicochemical, aesthetic, and some chemical parameters of raw, treated and tap water was analyzed. The analysis showed that drinking tap water has a good quality and was satisfactory according to the World Health Organization‘s (WHO) guidelines for drinking water. However, an assessment of consumers‘ perception of water consumption profiles revealed that 25 % of the respondents claimed that the water quality was bad and had some taste that may be attributable to the long period of water storage. Therefore, it is recommended that the post chlorination dose should be increased to ensure the disinfection requirements and avoid any post-treatment contamination.